HEALTH PROMOTION EFFECTIVE VIA BOOKLET TO INCREASED TEEN KNOWLEDGE OF THE DANGERS OF SEXUALLY TRANSMITTED INFECTIONS IN SMAN 3 PALANGKA RAYA CITY BARRIERS IN 2022 - Tambunan, Lensi Natalia; Ningsih, Fitriani (Midwifery Departement Poltekkes Kemenkes Banjarmasin, 2023)
Adolescence is the transition of childhood to adulthood, which is marked by biological changes., Psychological change., and social changes.Sexually transmitted infections are infections caused by germs like mushrooms, It's a virus., And parasites that enter and breed inside the sexually transmitted body. Reproductive health information has an impact on teen sexual life. Sexually transmitted infections can cause many negative effects both physically, psychosocial, Not even financially.Lack of information about reproductive health, both from parents and school to determine the low level of knowledge of young people about sexually transmitted infections. The purpose of research to know the effectiveness of health promotion through Booklet to increased teen knowledge of the dangers of sexually transmitted infections. This research uses pre-experimental design, design type is one group pretest-postet, The sample in this study is 53 responders. It's the class of x SMAN 4 Palangka Raya..Sample fetching purposive sampling using inclusion criteria.Data analysis uses paired samples t-test. Paired test results t-tests (p value = 0,000 & lt; 0.05 ), Which means there's an effective health promotion through Booklet towards increased teen knowledge.The conclusion in this study is that the use of Booklets as health - promotion media can get information in a short time so that it can increase adolescent knowledge.